Can Life in Senior Care Homes Affects Psychological Well-Being of Older Widows - Madhavi B.M.; Jamuna D.; Srikanth Reddy V. (International Journal of Indian Psychȯlogy, 2022)
In the era of modernization, with the transmission of values and morality, widows face several societal challenges. Illiteracy and economic dependency intensify the situation of these widows as they grow older. Widows their psychological, emotional and physical health has been affected due to chronic psychological distress. The objective of this present study is to examine the life experiences of older widows living in senior care homes and its impact on psychological wellbeing.  The study was carried out on 160 older widows who are residing in pay and stay homes in the age group of 65-75 years, who are cognitively intact and communicative   were enrolled in the study. The findings revealed that age, no education, lower income and joint family are the sources of psychological distress in older widows.  Poor health appears to be an important factor among the institutionalized aged to effectively determine whether the individual can cope with major stresses.